Mdka expression is associated with quiescent neural stem cells during constitutive and reactive neurogenesis in the adult zebrafish telencephalon - Lübke, Luisa; Zhang, Gaoqun; Strähle, Uwe; Rastegar, Sepand (Brain Sciences, 2022)
In contrast to mammals, adult zebrafish display an extraordinary capacity to heal injuries and repair damage in the central nervous system. Pivotal for the regenerative capacity of the zebrafish brain at adult stages is the precise control of neural stem cell (NSC) behavior and the maintenance of the stem cell pool. The gene mdka, a member of a small family of heparin binding growth factors, was previously shown to be involved in regeneration in the zebrafish retina, heart, and fin. Here, we investigated the expression pattern of the gene mdka and its paralogue mdkb in the zebrafish adult telencephalon under constitutive and regenerative conditions. Our findings show that only mdka expression is specifically restricted to the telencephalic ventricle, a stem cell niche of the zebrafish telencephalon. In this brain region, mdka is particularly expressed in the quiescent stem cells. Interestingly, after brain injury, mdka expression remains restricted to the resting stem cell, which might suggest a role of mdka in regulating stem cell quiescence.